Geology and Petrogenesis of Igneous Rocks from Batur Paleovolcano, Gunungkidul, Yogyakarta: Evidence from their Textures, Mineralogy, and Major Elements Geochemistry - Fahmi Hakim; Yanuardi Satrio Nugroho; Cendi Diar Permata Dana; Anastasia Dewi Titisari (Journal of Applied Geology, 2019)
Batur paleovolcano is located in Wediombo Beach area, Gunungkidul Regency, Yogyakarta and is being part of Wuni Formation. Several volcanic products including lava flow, autoclastic breccia and volcanic breccia can be found associated with diorite intrusions. This research is aimed to characterize geological, mineralogical andgeochemical variations of igneous rocks from Batur paleovolcano to understand its petrogenesis. Detailed geological mapping with scale of 1:12,500 is conducted to identify geological aspects and delineate igneous rocks distributions. Igneous rocks and selected wall rocks samples were prepared for laboratory analysis including 8 samples for petrography and 5 samples for ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry) analysis. Several geochemical data from previous study are also added to investigate the geochemical variations. Geological condition of the research area consists of four rock units including colluvial deposit, limestone, andesite lava and diorite intrusion. Geological structures found are normal fault and shear joint where the main stress direction is north–south. Petrography analysis showed that igneous rocks in this research area consist of diorite intrusion and andesite lava with phorphyritic texture. Plagioclase become the most abundant minerals found both as phenocryst phase and groundmass. Hornblende only occur as phenocryst phase in minor amounts as accesory mineral. Major elementsgeochemistry analysis showed the rocks are characterized by intermediate silica with low alkali content. They are can be categorized as calc-alkaline series. However, some samples are fall into tholeiitic series. Major elements variation and textural study also indicate the magma is experienced differentiation process by fractional crystallization mechanism. This study suggests that igneous rocks from Batur paleovolcano is formed by two phases of formation. Earlier phase is the formation of andesite lava in island arc tholeiitic tectonic setting then at the later phase is formation of diorite intrusion in the calc-alkaline basalts tectonic setting.